Halogenated graphenes: rapidly growing family of graphene derivatives - Karlický, František; Kumara Ramanatha Datta, Kasibhatta; Otyepka, Michal; Zbořil, Radek (ACS nano, 2013)
Graphene derivatives containing covalently bound halogens (graphene halides) represent promising two-dimensional systems having interesting physical and chemical properties. The attachment of halogen atoms to sp(2) carbons changes the hybridization state to sp(3), which has a principal impact on electronic properties and local structure of the material. The fully fluorinated graphene derivative, fluorographene (graphene fluoride, C1F1), is the thinnest insulator and the only stable stoichiometric graphene halide (C1X1). In this review, we discuss structural properties, syntheses, chemistry, stabilities, and electronic properties of fluorographene and other partially fluorinated, chlorinated, and brominated graphenes. Remarkable optical, mechanical, vibrational, thermodynamic, and conductivity properties of graphene halides are also explored as well as the properties of rare structures including multilayered fluorinated graphenes, iodine-doped graphene, and mixed graphene halides. Finally, patterned halogenation is presented as an interesting approach for generating materials with applications in the field of graphene-based electronic devices.
Keywords: Vibration; Tissue Engineering; Semiconductors; nanostruktury; polovodiče; Electrons; Nanostructures; Absorption; Stress, Mechanical; lidé; brom; Humans; Materials Testing; Bromine; Animals; Halogens; Graphite; Fluorine; vibrace; Polymethyl Methacrylate; Spectrum Analysis, Raman; grafit; Chlorine; zvířata; testování materiálů; mechanický stres; Nanotechnology; chlor; elektrony; tkáňové inženýrství; absorpce; termodynamika; fluor; nanotechnologie; Ramanova spektroskopie; polymethylmethakrylát; halogeny; Thermodynamics